2005
DOI: 10.1530/eje.1.01862
|View full text |Cite
|
Sign up to set email alerts
|

Plasma chromogranin A in patients with autoimmune chronic atrophic gastritis, enterochromaffin-like cell lesions and gastric carcinoids

Abstract: Objective: In atrophic body gastritis (ABG) chronic hypergastrinaemia stimulates enterochromaffinlike (ECL) cell proliferation with development of cell hyperplasia, dysplasia and possibly type-1 gastric carcinoids. As circulating chromogranin A (CgA) levels are a marker of neuroendocrine tumours, we evaluated the clinical usefulness of CgA assay in ABG patients to detect those with carcinoids. Design and methods: Plasma CgA levels were measured using a commercial ELISA in 45 healthy volunteers, nine patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 27 publications
4
58
0
1
Order By: Relevance
“…The possible explanation for this finding can be the effect of gastrin on gastric ECL cells because it is stated that ECL cell mass is a major determinant of CgA elevation in hypergastrinemic conditions (19). It has been reported that CgA is widely expressed in neuroendocrine cells (9) and in AIG patients, the serum CgA level is affected by gastrin secretion from antral gastrin-releasing cells (23). This finding may help explain why some patients without ECL cell hyperplasia have increased serum CgA levels.…”
Section: Discussionmentioning
confidence: 95%
“…The possible explanation for this finding can be the effect of gastrin on gastric ECL cells because it is stated that ECL cell mass is a major determinant of CgA elevation in hypergastrinemic conditions (19). It has been reported that CgA is widely expressed in neuroendocrine cells (9) and in AIG patients, the serum CgA level is affected by gastrin secretion from antral gastrin-releasing cells (23). This finding may help explain why some patients without ECL cell hyperplasia have increased serum CgA levels.…”
Section: Discussionmentioning
confidence: 95%
“…Research has shown that the level of serum CgA is higher than normal in 81% of patients with neuroendocrine carcinoma, and it has therefore been suggested as a conventional tumor marker [21]. However, caution is required, since the level of serum CgA may also be higher than normal in some cases of benign diseases such as chronic gastritis [22]. For colorectal tumor patients with endocrine symptoms, the hormone corresponding to the patient's symptoms should be monitored, along with its precursors or metabolites; this could play an important role in diagnosis, guiding the treatment and the assessment of tumor growth and recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…2). Other conditions with elevated levels of CgA are seen in patients with impaired kidney function or chronic atrophic gastritis type A, or in those treated with proton pump inhibitors ( Table 2; Hsiao et al 1990, Sanduleanu et al 1999, Giusti et al 2004, Peracchi et al 2005, O'Toole et al 2009). However, while none of these parameters affect the measurement of CgB, there are as yet no commercially available assays for CgB (Stridsberg et al 2005, O'Toole et al 2009).…”
Section: General Markers Chromograninsmentioning
confidence: 99%